Study of Mineral Extraction by Various Geotechnological Methods - Aliyeva, M.H.; Aliyarova, Kh.E.; Mammadova, S.B. (Herald of Azerbaijan Engineering Academy, 2024)
In recent years, deposits and manifestations of various genetic types (copper-porphyry, coppercoalch, copper sandstone, etc.) have been discovered in the territory of the Nakhchivan Autonomous Republic (Diakhchay, Yalinlig, Goydag, Goygol, Nasirvaz, etc.). However, in most of these fields, the discovered reserves and forecast resources were considered out of balance for exploitation by conventional methods. Experiments show that the development of this type of copper deposits by the geotechnological - underground mining method gives economically efficient results. In the article, it is recommended to process these deposits by the etching method. Reagents are offered to perform etching. The technical economic indicators obtained during wear are interpreted.